Ensemble molecular mimicry correlates with antibody cross-reactivity in proteome-wide studies - Wrabl, James O.; Beale, Josh; Fortunato, Gabriel; Monsalve, Antonieta van den Berg; Hilser, Vincent J. (Frontiers in Immunology, 2026)
Energetics of protein–protein binding necessarily include contributions both from conformational equilibria and from interfacial interactions. In the particular case of an antibody binding to a protein epitope, the conformational contribution is typically neglected as the antibody-bound and free forms of the protein are usually highly similar, leading to the reasonable conclusion that binding affinity in most cases can be reconciled in the context of observed interfacial interactions. However, the phenomenon of molecular mimicry has also been widely observed, wherein antibodies raised against one sequence/structure are able to recognize a completely different sequence/structure. This observation suggests that, in some cases, the conformational contribution could play a significant role in facilitating this cross-reactivity. Here, this conjecture is supported, utilizing a recent discovery that permits evaluation of the thermodynamic compatibility of any sequence for the conformational ensemble of any other protein—in effect providing direct access to the conformational contribution to binding. The importance of the contribution could then be assessed on a proteome-wide scale, in the context of the unexpected cross-reactivity observed when the human proteome is challenged with antibodies raised against a set of virus protein antigens. Because the virus protein antigens and the cross-reactive human proteins share substantial similarity when modeled as thermodynamic ensembles, despite the absence of detectable sequence or structural similarity, we hypothesize that these cross-reactive epitopes share a novel kind of immunological molecular mimicry, termed “ensemble molecular mimicry” (EMM). To investigate potential mechanisms, a sequence-based algorithm was developed to probe for the relationship between high scoring sequence segments and cross-reacting epitopes, and it was discovered that 9 of 11 medically relevant cross-reactive epitopes taken from the literature exhibited higher-than-expected local EMM values. Taken together, the results suggest that conformational equilibrium can affect affinity and that it is hypothetically possible for cross-reactive epitopes to share a pairwise thermodynamic signature, even in the absence of sequence or structural similarity.